The Origins of Islamic Jurisprudence: Meccan Fiqh Before the Emergence of Classical Schools - M. Irsyad Maulana; Yusuf Hanafi (Penerbit Goodwood, 2024)
Purpose: This study critically examines the development of early Islamic law in Mecca through an analysis of Harald Motzki’s The Origins of Islamic Jurisprudence: Meccan Fiqh Before the Classical Schools in 2002. It focuses on the scholarly contributions of ‘Ata’ ibn Abi Rabah and Ibn Jurayj in shaping Meccan fiqh in the second century Hijri and engages with historiographical debates on the authenticity of early legal traditions.Methodology: A qualitative library research design was employed. Data were obtained from systematic reviews of primary and secondary sources, including Motzki’s work, Musannaf ‘Abd al-Razzaq, and key studies by Schacht, Hallaq, Calder, and El-Shamsy. Thematic analysis was used to examine debates on isnad criticism, hadith authenticity, and socio-political influences on early Islamic legal development.Results: Motzki’s analysis demonstrates that legal transmissions from Ibn Jurayj to ‘Ata’ ibn Abi Rabah in Musannaf ‘Abd al-Razzaq are highly likely to be authentic. Variations in transmission styles, including legal reasoning, uncertainty, and alternative citations, make systematic fabrication implausible. Early Meccan fiqh is shown to be shaped by both revelatory sources and local socio-political contexts.Conclusions: Motzki provides a balanced alternative to extreme skepticism and traditionalist approaches, showing that early Islamic jurisprudence was a dynamic and context-based legal process prior to madhhab formation.Limitations: The study is limited to Motzki’s textual corpus and does not include comparative regional legal sources. Contributions: It contributes to Islamic legal historiography by demonstrating the value of the isn?d-cum-matn method in reassessing early legal authenticity.